Characterization of cholesterol efflux capacity in diabetic and non-diabetic patients with coronary artery disease: comparison between acute coronary syndrome and stable coronary artery disease. (14th October 2021) - Funabashi, S; Kataoka, Y; Ogura, M; Kuyama, N; Otsuka, F; Asaumi, Y; Noguchi, T
Abstract: Introduction: Type 2 diabetic patients more likely exhibit a lower high-density lipoprotein (HDL) level. Given a greater glycation and oxidative stress in diabetic subjects, these atherogenic characteristics could cause dysfunctional HDL including a reduced cholesterol efflux capacity (CEC), which may account for an increased risk of diabetic macrovascular disease including acute coronary syndrome (ACS). However, it remains to be fully elucidated characteristics of HDL-mediated CEC in type 2 diabetic patients, in association with clinical presentation of coronary artery disease (CAD). Purpose: To characterize CEC in CAD subjects with type 2 diabetes mellitus. Methods: The current study prospectively analyzed 87 statin-naive patients with CAD. CEC was measured by using the collected apolipoprotein B-depleted serum. Liquid scintillation counting (Perkin-Elmer Analytical Sciences, MA, US) was used to quantify the efflux of radioactive cholesterol from J774 cells. Clinical characteristics and CEC were compared in diabetic and non-diabetic subjects. Results: The averaged HbA1c in diabetic patients was 6.7±1.2, and 66.7% of them achieved HbA1c <7.0%. Diabetic subjects more likely exhibited a history of hypertension and dyslipidemia, and multi-vessel disease (Table). Moreover, a lower CEC level was observed in diabetic patients, accompanied by a lower HDL-C and apolipoprotein A-I levels with a higher level of triglyceride (Table). HDL-C (r=0.62, p-value<0.01) and Apolipoprotein A-I (r=0.70, p-value <0.01) were associated with CEC, whereas there was no significant difference in CEC between subjects with HbA1c <7.0% vs. ≥7.0% (0.74±0.07 vs. 0.78±0.08, p=0.22). On multivariate analysis, type 2 diabetes mellitus was an independent contributor to CEC <0.79 (median) (HR=2.75, 95% CI: 1.11–6.82, p=0.03). Interestingly in particular, CEC was substantially lower in diabetic patients with ACS compared to those with stable CAD (Figure). By contrast, clinical presentation of CAD did not affect CEC in non-diabetic subjects (Figure). Conclusions: A lower CEC level was observed in subjects with type 2 diabetes mellitus. In particular, this HDL functionality was profoundly diminished in those presenting ACS. Our findings suggest functionality of HDL as a potential therapeutic target in diabetic patients experiencing ACS. Funding Acknowledgement: Type of funding sources: None.